Nahdlatul Ulama’s Strategic Role in Shaping Indonesian Foreign Policy - Utama, Virdika Rizky (Universitas Islam Internasional Indonesia (UIII), 2024)
This article analyses the strategic influence of Nahdlatul Ulama (NU) on Indonesian foreign policy using constructivist theory and social identity theory as frameworks. It contends that NU's contributions are motivated by its intrinsic identity and principles, including the promotion of moderate Islam, rather than by external influences. This research utilizes the G20 Religion Forum (R20) and the ASEAN Intercultural and Interreligious Dialogue Conference (IIDC) as case studies to illustrate how NU capitalizes on its religious identity and principles to support Indonesia's diplomatic objectives of promoting peace, tolerance, and international collaboration. This study emphasizes the relationship between identity formation and policy results, illustrating NU as a crucial non-state participant in Indonesia's religious diplomacy.